Analisis Biaya dan Manfaat Penerapan Treasury Single Account Untuk Penerimaan Kas Negara Studi Kasus di Wilayah Daerah Khusus Ibukota Jakarta - , Saiful Anam; , Dr. Mamduh Mahmadah Hanafi, MBA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Treasury Single Account (TSA) of Receipt Account is a government effort to accelerate cash inflow for government cash receipt. Government implement TSA of Receipt Account as a form of cash management in order to reduce float or time delay in process of government cash receipt. The objective of this research is to test the additional costs and benefits of TSA implementation of Receipt Account in Jakarta Region compared with the Non TSA Policy. This research uses data of government cash receipt that be administrated by KPPNs in Jakarta Region. KPPNs receive data from banks/post office that receive cash for government receipt. Receipt data in 2010 be grouped based on the date of transferring receipt according to the rule of TSA implementation of Receipt Account. By using receipt data then be calculated additional costs and benefits of TSA implementation of Receipt Account. In order to make decision, test done by using parametric method and nonparametric method. For parametric test used Paired Sample t-Test and for nonparametric test used Wilcoxon Signed Ranks Test. Those tests done to know whether the additional benefits of TSA implementation is greater than its additional costs. The results of comparative statistical test between the additional costs and additional benefits of TSA implementation of Receipt Account show that both parametric test and nonparametric tests give conclusion that the additional benefits of TSA implementation of Receipt Account are greater than its additional costs. TSA implementation of Receipt Account in Jakarta Region is profitable for government. The result of this research contradicted with the previous research done in Yogyakarta Region that said TSA implementation of Receipt Account is more costly for government.